Gambaran Kesehatan Lingkungan dan Kejadian Stunting pada Anak Balita Usia 0-2 Tahun di Desa Ambesea Kecamatan Laeya Kabupaten Konawe Selatan - Helvinawati Helvinawati; Hartati Bahar; LA Ode Ahmad Saktiansyah (Jurnal Siti Rufaidah, 2025)
Background: Stunting remains a serious public health issue in Indonesia, particularly in rural areas such as Ambasea Village, Laeya Sub-district, South Konawe Regency. Stunting, or chronic growth failure in children due to prolonged malnutrition, generally occurs during the first 1,000 days of life. In Ambasea Village, this problem is exacerbated by irregular eating patterns among toddlers, consumption of low-nutrient foods, and poor hygiene behaviors. Toddlers frequently consume unhealthy snacks, reject main meals such as rice and side dishes, and rarely wash their hands with soap before eating or after using the toilet. Furthermore, limited access to basic sanitation—such as the lack of proper latrines and adequate wastewater disposal systems (SPAL)—also contributes to the high risk of infections that disrupt nutrient absorption, increasing the likelihood of stunting in children. Objective: This study aims to describe the environmental health conditions contributing to the incidence of stunting among children aged 0–2 years in Ambasea Village. Methods: The research used an observational analytic method with a quantitative cross-sectional design. The study involved 54 toddlers identified as stunted. Data were collected through structured interviews with parents or caregivers and direct observation of the household and surrounding environmental conditions. Results: The results showed that 66.5% of households did not have access to proper latrines, and 70% lacked adequate wastewater disposal systems. However, 87% had access to clean water, and 85% of respondents demonstrated good handwashing behavior. Conclusion: The environmental health conditions in Ambasea Village reveal ongoing challenges related to latrine ownership and wastewater management. Although clean water access is relatively good and hygiene practices among residents are fairly positive, improving sanitation infrastructure remains crucial. Enhancing these conditions is expected to significantly reduce the risk of stunting among toddlers in the area. Collaborative efforts involving local government, health workers, and the community are essential to create a healthier environment for early childhood development.